1998
DOI: 10.2307/3284715
|View full text |Cite
|
Sign up to set email alerts
|

Taenia crassiceps Cysticercosis: Humoral Immune Response and Protection Elicited by DNA Immunization

Abstract: The purpose of this study was to evaluate DNA vaccination in cysticercosis prevention by using a Taenia crassiceps cDNA of a recombinant antigen (KETc7) that has been reported as protective against murine cysticercosis. The KETc7 cDNA was cloned into the pcDNA3 plasmid alone or with the betaglycan signal peptide sequence (pTc-7 and pTc-sp7, respectively). Positive expression of the pTc-sp7 product was confirmed by transfection of C33 cells and immunofluorescence using sera of mice infected with T. crassiceps. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
16
0
4

Year Published

2001
2001
2015
2015

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 24 publications
1
16
0
4
Order By: Relevance
“…To test BLS as an adjuvant, another group of mice was immunized with BLS (25 g per mouse) with or without the synthetic peptide. The antigen doses were estimated according to previously published results (27). Mice under anesthesia with sevoflurane were orally immunized three times at 15-day intervals and challenged 2 weeks after the last immunization.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…To test BLS as an adjuvant, another group of mice was immunized with BLS (25 g per mouse) with or without the synthetic peptide. The antigen doses were estimated according to previously published results (27). Mice under anesthesia with sevoflurane were orally immunized three times at 15-day intervals and challenged 2 weeks after the last immunization.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, BLS has the ability to stimulate bone marrow-derived mouse dendritic cells in vitro through Toll-like receptor 4 (TLR4), upregulating costimulatory molecules (CD80 and CD86), activation molecules (CD40, major histocompatibility complex class II, mRNA levels of the chemokines macrophage inflammatory protein 1 [MIP-1], MIP-2, monocyte chemoattractant protein 1, RANTES), and the secretion of proinflammatory cytokines (3). All these properties possibly underlie the observed adjuvant capacity of BLS (27).…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…(Manoutcharian et al 1996;Manoutcharian reference 2004;Rosas et al 1998;Toledo et al 1999; In the peptide KETc7 2 protective epitopes GK1 and PT1 of 18 and 10 aminoacids respectively were identified ). These peptides belong to different developmental stages of Taenia crassiceps and Taenia solium (Toledo et al 1999;Rosas et al 1998Rosas et al , 2002Sciutto et al 1995Sciutto et al , 2008 and are found in different anatomical structures of the cysticerci, in the eggs and in the adult taeniae. Their sequences are detected in both cestodes with minimal differences in certain aminoacids which do not modify their tridimensional structure nor their protective capacity (Rassy et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Various degrees of protection have been reported; it has been demonstrated that living oncospheres and oncospheral antigens are the most effective (Flisser et al 1979, Lightowlers 1994. Recently the use of recombinant proteins and DNA as vaccines against rodent, ovine and bovine cysticercosis has been used with high degrees of immunity (Johnson et al 1989, Harrison et al 1996, Rosas et al 1998, CruzRevilla et al 2000.…”
mentioning
confidence: 99%